IMPLEMENTATION OF THE TEAM ASSISTED INDIVIDUALIZATION LEARNING MODEL TO IMPROVE THE ACTIVITIES AND LEARNING OUTCOMES OF CRAFTS AND ENTREPRENEURSHIP FOR CLASS XI STUDENTS AT RATNA WARTHA VOCATIONAL SCHOOL FOR THE 2022/2023 ACADEMIC YEAR - Ni Made Sri Wahyuni (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2023)
This research aims to determine the economic learning outcomes of class This type of research is Classroom Action Research (PTK) which is carried out in two cycles, where each cycle consists of four meetings, each meeting for presentation of material and one meeting for evaluating student learning outcomes. The subjects of this research were Class XI AP 2 SMK Ratna Wartha for the 2022/2023 academic year, totaling 33 students. The results of the first cycle of research where the number of students who completed was 19 students (57.58%) and those who did not complete were 14 students (42.42%). Student learning activity in cycle I was 49.61% with an average value of student learning outcomes of 74.57, absorption capacity of 74.57% and classical completeness reaching 57.58%. In cycle II the number of students who completed was 29 students (87.88%) and those who did not complete were 4 students (12.12%), where students who did not complete were given additional assignments in the form of individual assignments to complete the grades of students who did not complete. . The average student learning activity in cycle II reached 79.53% with an average learning outcome value of 79.54, absorption capacity of 79.54% and classical completeness of 87.88%.